Analisis Koordinasi Antar SKPD dalam Penataan dan Pemberdayaan PKL : Studi Kasus Kota Sukabumi: (Analysis of Coordination Among Local Government Agencies in the Management and Empowerment of Street Vendors: A Case Study of Sukabumi City) - Andi Mulyadi; Dian Purwanti; Ratna Istianah; Kalinda Oktafiani (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to analyze the coordination among Regional Government Agencies (SKPD) in the management and empowerment of Street Vendors (PKL) in Sukabumi City. The study is motivated by the efforts of the Sukabumi City Government to maintain public order, improve the quality of public spaces, and support the sustainability of community economic activities. Although the government has relocated street vendors to designated areas, many vendors continue to return to the city center, highlighting the need for effective coordination among the agencies involved. This study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation involving informants from the Municipal Police (Satpol PP), the Department of Cooperatives, Micro, Small and Medium Enterprises, Industry and Trade (Diskumindag), the Transportation Agency, and Cikole Subdistrict Office. Informants were selected using purposive sampling and snowball sampling techniques. Data analysis was conducted using Chandra Bose’s coordination theory, which includes clearly defined goals, clear lines of authority and responsibility, comprehensive policies, cooperation, communication, leadership, and supervision. The findings indicate that coordination among regional government agencies in the management and empowerment of street vendors in Sukabumi City has been relatively effective. This is reflected in shared objectives, a clear division of responsibilities, inter-agency cooperation, adaptive communication, and leadership support that fosters synergy among stakeholders. However, several challenges remain, including limited human resources, the absence of standardized coordination mechanisms, discrepancies in data among agencies, and limited relocation sites for street vendors. Therefore, strengthening a structured and sustainable coordination system is necessary to enhance the effectiveness of street vendor management and empowerment in Sukabumi City.